2013
DOI: 10.1002/pola.26801
|View full text |Cite
|
Sign up to set email alerts
|

Octahydrogenated retinoic acid‐conjugated glycol chitosan nanoparticles as a novel carrier of azadirachtin: Synthesis, characterization, and in vitro evaluation

Abstract: Environment‐friendly and controlled release formulation is highly promising for reducing environmental pollution and achieving the most effective utilization of pesticides. As a novel “green” nanocarrier of pesticides, amphiphilic self‐assembled nanoparticles were prepared by chemical conjugation of octahydrogenated retinoic acid (OR) to the backbone of glycol chitosan (GC). In aqueous media, the synthesized OR‐GC conjugates formed nanosized particles with a diameter of 257 nm. Hydrophobic azadirachtin (AZA) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Instead, nanoparticles can be used to increase the solubility, thus reducing the toxicity. To date, low-water-soluble insecticides have been successfully loaded into modified chitosan [45][46][47]63] and porous silica [50]. However, none of these studies tested for reduced environmental toxicity.…”
Section: Nanoparticles As Carriers For Insecticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, nanoparticles can be used to increase the solubility, thus reducing the toxicity. To date, low-water-soluble insecticides have been successfully loaded into modified chitosan [45][46][47]63] and porous silica [50]. However, none of these studies tested for reduced environmental toxicity.…”
Section: Nanoparticles As Carriers For Insecticidesmentioning
confidence: 99%
“…However, none of these studies tested for reduced environmental toxicity. Using modified chitosan nanoparticles to load the hydrophobic insecticide azadirachtin, Lu et al [47] showed favorable inhibition of cell proliferation in S. litura ovarian cell lines, and sustained drug release. In another study, Liu et al [55] showed an increase in uptake and higher mortality when H. armigera larvae were subjected to dendrimers loaded with hydrophobic thiamethoxam.…”
Section: Nanoparticles As Carriers For Insecticidesmentioning
confidence: 99%
“…The increased cost and toxicity of low water-soluble insecticides can be minimised by the use of NPs as carriers which can increase the solubility ( Campos et al, 2018 ). Several studies have reported the use of NPs for the smart delivery of various insecticides ( Lu et al, 2013 ; Zhang et al, 2013 ; Wang Y. et al, 2014 ; Campos et al, 2018 ). Lu et al (2013) demonstrated the role of CS-NPs as a carrier for azadirachtin for the sustained release of insecticide.…”
Section: Role Of Nanotechnology In Crop Protectionmentioning
confidence: 99%
“…Several studies have reported the use of NPs for the smart delivery of various insecticides ( Lu et al, 2013 ; Zhang et al, 2013 ; Wang Y. et al, 2014 ; Campos et al, 2018 ). Lu et al (2013) demonstrated the role of CS-NPs as a carrier for azadirachtin for the sustained release of insecticide. An increase in uptake and higher toxicity of thiamethoxam insecticide was reported against Helicoverpa armigera larvae when intercalated with dendrimer NPs ( Liu X. et al, 2015 ).…”
Section: Role Of Nanotechnology In Crop Protectionmentioning
confidence: 99%
“…Surface-functionalized vertically arranged carbon nanofibers act as molecular cargo and carry the plasmid DNA to the Table 4. Nano-protectant with insecticidal activity [53][54][55][56][57][58][59]. Table 3.…”
Section: Application Of Nanoparticles In Gene Delivery System Andmentioning
confidence: 99%